Concepções de educação ambiental de professoras de geografia da rede municipal de ensino de Goiânia: tendências reveladas - ALVES, Silvia de Freitas (2008)
The Environmental Education is thought as Education, in their several dimensions, as in the education space no-formal, the community, as in the formal-the school. This way, the theoretical and methodological elements, that base the activities of Environmental Education in the teaching of Geography deserve reflection and analysis. The purposed of this work is to investigate the theoretic and methodological references used in practice of the Environmental Education for the Geography s teachers of the second and third cycles of human development of located municipal schools in the south area of Goiânia. For so much, it is necessary: to draw the teachers profile, detaching elements of their formation and of their educational work; to observe the professionals educational practice and to identify contents, categories and the geographical concepts used in their pedagogic practices. Some questions are listened as: how to work with the fragility of the Environmental Education in the schools with pedagogic practice and which would the procedures roads and the most appropriate tendencies be to develop it? The investigation method adopted in the research it is historic-dialetic. It is agreed that the logical construction of the materialistic method historic-dialetic was presented as a theoric possibility of interpretation of the education and environmental realities. The methodology of the research is qualitative, with the use of the instruments: questionnaires, semi-structured interviews and empiric observation. It is possible to understand the theoretic and methodological foundations which the teachers of Geography have been based for the exercise of their profession on what says respect to the Environmental Education, once the paradigms of interpretation of the reality interfere in the pedagogic work and they affect directly what intend to teach. It is expect to contribute with the development of expressive practices of Environmental Education, accompanied of critics reflexions that, they can work the educational value of the Geography as well as to demonstrate necessity to implant politics of teachers formation directly to the Environmental Education. In additin to possibility possible the teachers training of Geography, and consequently, the improvement in the quality of teaching of the municipal schools of Goiânia city.